2007
DOI: 10.3844/ajabssp.2007.123.129
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of a Poultry Isolate Salmonella enteritidis on Egg Vitelline Membrane: Survival and Growth in Egg Components after Different Refrigeration Storage Times

Abstract: An in vitro study was designed to determine the extent of Salmonella enterica serovar enteritidis survival and growth permissiveness in egg components isolated from shell eggs held at refrigeration temperature over an 8 week time period. Eggs were collected from a commercial laying facility at one-week intervals for eight weeks and stored at refrigeration temperature. After storage, eggs were dipped in ethanol, cracked aseptically and separated into yolk and albumen samples. S. enteritidis resistant to novobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Howard et al (2006) demonstrated that S. Typhimurium could survive within the egg and even exhibit net growth during 8 weeks of storage, even under refrigeration conditions. In further studies, Howard et al (2007) inoculated egg components with S. Enteritidis and observed the survival and growth of the bacterium as related to refrigerated storage time for 8 weeks. Although they found no evidence of vitelline membrane deterioration leading to yolk contamination during the storage period they did observe survival of S. Enteritidis on the vitelline membrane and in the albumen, and in some instances they did note net growth of the pathogen (Howard et al, 2007).…”
Section: Horizontal Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howard et al (2006) demonstrated that S. Typhimurium could survive within the egg and even exhibit net growth during 8 weeks of storage, even under refrigeration conditions. In further studies, Howard et al (2007) inoculated egg components with S. Enteritidis and observed the survival and growth of the bacterium as related to refrigerated storage time for 8 weeks. Although they found no evidence of vitelline membrane deterioration leading to yolk contamination during the storage period they did observe survival of S. Enteritidis on the vitelline membrane and in the albumen, and in some instances they did note net growth of the pathogen (Howard et al, 2007).…”
Section: Horizontal Transmissionmentioning
confidence: 99%
“…In further studies, Howard et al (2007) inoculated egg components with S. Enteritidis and observed the survival and growth of the bacterium as related to refrigerated storage time for 8 weeks. Although they found no evidence of vitelline membrane deterioration leading to yolk contamination during the storage period they did observe survival of S. Enteritidis on the vitelline membrane and in the albumen, and in some instances they did note net growth of the pathogen (Howard et al, 2007). This research supports the need for rapid refrigeration and maintenance of the cold chain during storage.…”
Section: Horizontal Transmissionmentioning
confidence: 99%